Rate of pancreatic cancer following a negative endoscopic ultrasound and associated factors - King, Dominic; Kamran, Umair; Dosanjh, Amandeep; Coupland, Ben; Mytton, Jemma; Leeds, John S.; Nayar, Manu; Patel, Prashant; Oppong, Kofi W.; Trudgill, Nigel J. (Endoscopy, 2022)
Background Data are limited regarding pancreatic cancer diagnosed following a pancreaticobiliary endoscopic ultrasound (EUS) that does not diagnose pancreatic cancer. We have studied the frequency of, and factors associated with, post-EUS pancreatic cancer (PEPC) and 1-year mortality.Methods Between 2010 and 2017, patients with pancreatic cancer and a preceding pancreaticobiliary EUS were identified in a national cohort using Hospital Episode Statistics. Patients with a pancreaticobiliary EUS 6–18 months before a later pancreatic cancer diagnosis were the PEPC cases; controls were those with pancreatic cancer diagnosed within 6 months of pancreaticobiliary EUS. Multivariable logistic regression models examined the factors associated with PEPC and a Cox regression model examined factors associated with 1-year cumulative mortality.Results 9363 pancreatic cancer patients were studied; 93.5 % identified as controls (men 53.2 %; median age 68 [interquartile range (IQR) 61–75]); 6.5 % as PEPC cases (men 58.2 %; median age 69 [IQR 61–77]). PEPC was associated with older age (≥ 75 years compared with < 65 years, odds ratio [OR] 1.42, 95 %CI 1.15–1.76), increasing co-morbidity (Charlson co-morbidity score > 5, OR 1.90, 95 %CI 1.49–2.43), chronic pancreatitis (OR 3.13, 95 %CI 2.50–3.92), and diabetes mellitus (OR 1.58, 95 %CI 1.31–1.90). Metal biliary stents (OR 0.57, 95 %CI 0.38–0.86) and EUS-FNA (OR 0.49, 95 %CI 0.41–0.58) were inversely associated with PEPC. PEPC was associated with a higher cumulative mortality at 1 year (hazard ratio 1.12, 95 %CI 1.02–1.24), with only 14 % of PEPC patients (95 %CI 12 %–17 %) having a surgical resection, compared with 21 % (95 %CI 20 %–22 %) of controls.Conclusions PEPC occurred in 6.5 % of patients and was associated with chronic pancreatitis, older age, more co-morbidities, and specifically diabetes mellitus. PEPC was associated with a worse prognosis and lower surgical resection rates.